Normalization of Spinal Cord Displacement With the Straight Leg Raise and Resolution of Sciatica in Patients With Lumbar Intervertebral Disc Herniation: A 1.5-year Follow-up Study. Issue 15 (1st August 2019) - Pesonen, Janne; Rade, Marinko; Könönen, Mervi; Marttila, Jarkko; Shacklock, Michael; Vanninen, Ritva; Kankaanpää, Markku; Airaksinen, Olavi
Abstract : Study Design: A controlled radiologic follow-up study. Objective: The aim of this study was to ascertain whether changes in cord excursion with straight leg raise test (SLR) at 1.5-year follow-up time accompany changes in clinical symptoms. Summary of Background Data: Lumbar intervertebral disc herniation (LIDH) is known to be a key cause of sciatica. Previously, we found that a significant limitation of neural displacement (66.6%) was evident with the SLR on the symptomatic side of patients with subacute single level posterolateral LIDH. Methods: Fourteen patients with significant sciatic symptoms due to a subacute single-level posterolateral LIDH were reassessed clinically and radiologically at 1.5 years follow-up with a 1.5T MRI scanner. Displacement of the conus medullaris during the unilateral and bilateral SLR was quantified reliably with a randomized procedure and compared between SLRs and to data from baseline. Multivariate regression models and backward variable selection method were employed to identify variables more strongly associated with a decrease in low back pain (LBP) and radicular symptoms. Results: Compared with previously presented baseline values, the data showed a significant increase in neural sliding in all the quantified maneuvers ( P ⩽ 0.01), and particularly of 2.52 mm ( P ⩽ 0.001) with the symptomatic SLR. Increase in neural sliding correlated significantly with decrease of both radicular symptoms (Pearson = -0.719, P ⩽ 0.001) and LBP (Pearson = -0.693, P ⩽ 0.001). Multivariate regression models and backward variable selection method confirmed the improvement of neural sliding effects ( P ⩽ 0.004) as the main variable being associated with improvement of self-reported clinical symptoms. Conclusion: To our knowledge, these are the first noninvasive data to objectively support the association between increase in magnitude of neural adaptive movement and resolution of both radicular and LBP symptoms in in vivo and structurally intact human subjects. Level of Evidence: 2 Abstract : We show noninvasively data to objectively support the association between improvement of neural adaptive movement and resolution of clinical symptoms in in vivo and structurally intact human subjects with clinically and radiologically proven posterolateral lumbar intervertebral disc herniation.